Tsunami Modeling on the Coast of Kwandang Bay, North Gorontalo District Using The Commit Application - Demulawa, Meilan (Peneliti.net, 2023)
Modeling a tsunami measuring 8.5 SR using ComMIT software. The simulation results include data on wave arrival time, wave depth and maximum height at three coastal locations in North Gorontalo, namely Tomilito, Kwandang and Ponelo Islands Districts. In tsunami modeling in Kwandang Bay, there are differences in wave heights on three beaches in the North Gorontalo region, including Tomilito, Ponelo and Kwandang. On the coast of Tomilito District, the maximum tsunami height reached 11 meters. Meanwhile, on the coast of Kwandang District, the tsunami height reached 10 meters, and the lowest tsunami height occurred on the Ponelo coast with a height of 9 meters